Diseño de la defensa ribereña de Shanao - Coral Falcón, Henry (1998)
This paper has been prepared, taking into account all · fundamental aspects of disasters which includes the province of Lamas, why it has seen fit to divide it into two parts; the first framing all the theoretical process of Risk Analysis 1 and Province Second it is showing the physical part of that analysis through a Civil Works project. The development models implemented by history in the province of Lamas, respond more to strategies and requirements extraprovincial stop the development of each community and increasing conditions Vulnerability. Thus you can see that the province capital is completely disjointed in their districts. This reality prompted to perform a study of risk analysis for prevention and mitigation Natural effects like El Niño. For Risk Analysis (Part One) we start from the analysis of the Threats identified from the inventory of historical disasters, · obtained the physical characteristics of the population centers in the area influence of those phenomena classified as dangerous threats. All this led to a series of processes that were classified prioritization threats, opportunities, capabilities, vulnerabilities and critical districts, to result in solving strategies such as: • Programs Prevention and mitigation of natural phenomena. • Improvement, Rehabilitation and Construction of Educational Infrastructure and Services. • Strengthening civil defense committee. • Improvement of Economic Income of the Population. • Improving the social conditions of life of the population. All these strategies Settlement, I took the first point Como study, to be in line with the profession. No doubt all districts of the province of Lamas Present Vulnerability of certain natural actions and is precisely where the Analysis reenters to carve, to result m of critical District Shanao the community. It is here where the second part of the work begins, manifested Through the design of a Civil Works, which will mitigate the Presence of Flooding in the village of Shanao caused by the Mayo River. Engineering design without just means, but also the Ministry of Economy, in such SENSE project formulation, has had to choose Elements Very Different son conventional (reinforced concrete) As the Gabions, DUE A son These flexible and cheap Mas. It is shown in this part; : In addition to the Features, Types, Forms of construction, specifications and applications gabions, the parameters taken to consider the type of defense waterfront (Breakwaters and embankments) and His lngenieril subsequent design. For the design of the waterfront Shanao defense, I was taken into account Basic information of Topography, rainfall, soil mechanics, Flow Rates Maximum avenues and history of the morphology of the Mayo River in this part of the province. Robert Manning's formula plays very important role of the UN in Obtaining the height of the retaining wall, while the base is in Depending on the height of Defense and density of the gabions. Finally Conclusions and Recommendations base is made, the Risk Analysis and a coastal defense with gabions.